Formulations, Politeness and Facework in Courtroom Interaction: A Study Case - Hagemeyer Burgo, Vanessa (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2023)
This article aims to analyse how formulations, politeness, and facework are employed by speakers to achieve specific purposes in courtroom interaction. The theoretical framework is based on the concepts of conversation analysis and forensic linguistics, and the corpus consists of the trial of Jodi Ann Arias, which received widespread media attention in the United States. The excerpts under analysis were taken from the final day of the prosecutor’s cross-examination and from a reporter’s transcript of proceedings, both available on the Internet. It is important to highlight that these devices contribute to construct, enhance, threaten, or weaken people’s image involved in this kind of context.